Approaches in Overcoming Economic Uncertainty in the Southeast Asian Region: Critical Review - Fianto, Achmad Yanu Alif (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2023)
This study analyzes the use of economic and financial theory to address economic uncertainty in Southeast Asia. The findings show a uniform approach between countries in economic stability policies, including financial stimulus for the MSMEs sector. This research also reveals a similar pattern in financial stimulus policies in six important sectors. Other efforts include creative industry incentives, road maps, training, and partnerships with investors. This research makes an important contribution in understanding the application of economic and financial theory in dealing with economic uncertainty in Southeast Asia. The findings can be a reference for other countries facing similar challenges